Dibalik Topeng Penyanyi Campursari (Studi Kasus pada Penyanyi Campursari Anjas Gitarani dan Tini Sebloh di Surakarta) - Handoko, Dwi (Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract In facing the intense competition in the music world, a number of singers have made various efforts to maintain their existence in the music world. Singers who face intense competition in the music world include Anjas Gitarani and Tini Sebloh. This research method is descriptive qualitative. The results of this study are: 1) Masks are used as a means to create innovation and creativity, not only as a face covering instrument. Anjas and Tini provide an overview of how creativity and innovation can create creativity to maintain their consistency in singing. 2) Anjas and Tini's vocal quality is actually quite ordinary. However, Anjas and Tini highlighted their stage action by wearing masks when performing on stage. 3). The mask is basically a tool that is used as a face cover. Someone wears a mask so that their real face is not visible. Mask is synonymous with the activity of